Glossy topcoat exterior paint formulations using water-based polyurethane/acrylic hybrid binders - Aznar, Alberto Carlos (2006)
The development of glossy topcoat one-pot exterior paint formulations using water-based polyurethane/acrylates hybrid binders as well as the assessment of its properties through different conventional tests is discussed in this work. Polyurethane (PU) anionomer having 2-ethoxymethacrylate terminal groups was prepared following a prepolymer mixing process. This prepolymer was chain extended in aqueous solution and after addition of acrylic monomers radical polymerized. Paints were prepared using titanium dioxide as unique pigment. Panels coated with air-dried paints with three pigment to volume concentration (PVC) values were subjected to standardized tests including adhesion, flexibility, gloss and color determination. Accelerated weathering tests were carried out to evaluate changes in properties, especially gloss and color, of painted panels. Solvent-based acrylic and polyurethane paints were included as high gloss quality reference coatings. It was found that air-dried formulations based on hybrid polyurethane/acrylic with up to 50 wt.% of acrylic component, show a gloss as high as 70 and the relative gloss change after accelerated weathering test is lower than the pure solvent-based acrylic and polyurethane paints.